Myth in modern media management and marketing - Kreft, Jan; Kuczamer-Klopotowska, Sylwia, 1971-; Kalinowska-Zeleznik, Anna, 1971- (Business Science Reference, 2020)
"This book analyzes the role of myth in management and marketing on the new media organization market. It also examines the media environment created by organizations, users and media recipients, as well as algorithms, codes and protocols"--